Aerodynamic admittance of a 6:1 rectangular cylinder: A computational study on the role of turbulence intensity and integral length scale. Issue 218 (November 2021) - Li, Weilin; Patruno, L.; Niu, Huawei; de Miranda, Stefano; Hua, Xugang
Abstract: The evaluation of the aerodynamic admittance is a fundamental step in the calculation of the buffeting response of flexible structures immersed in turbulent flows such as long-span bridges and slender towers. As it is well-known, bluff sections immersed in turbulent flows often exhibit a complex aerodynamic behavior, which can be greatly affected by the turbulence intensity and the integral length scales of the impinging turbulence. In this paper, computational fluid dynamics is used for the evaluation of the admittance functions of a 6:1 rectangular cylinder. Firstly, the incoming turbulence is synthetically generated. Then the aerodynamic admittance functions are evaluated considering five different inflow conditions using Large Eddy Simulations. The use of synthetic inflows allows to easily separate the role played by each characteristic of the inflow turbulence, so allowing to separately study the effect of the turbulence intensity and the length scales. Highlights: The aerodynamic admittance of a 6:1 rectangular cylinder is studied using LES. Five synthetic inflow conditions are generated. The effects of the incoming turbulence intensity and integral scales are separately considered. The spatial distribution of the sectional admittance is detailed.